Development cycle of selected strains of aedes aegypti (linnaeus) based on water temperature and type of containers / Farah Izzati Mohammad Sabri - Mohammad Sabri, Farah Izzati (2017)
Vector borne diseases has been partially associated with the current changes of global warming which can be included water temperatures and type of containers. This study was conducted to determine the effect of increase water temperature on the development of Aedes aegypti immatures under laboratory condition using temperature regulated water bath to cover a range of temperature from 25°C to 35°C. Two experiments were designed: (1) for local strain of Aedes aegypti (SEL-strain, JHR-strain, and SBH-strain) and four types of container under setting temperature regimes. The containers that were collected are tire, plastic, glass and coconut shell. The experiments were conducted under presence of larvae food. The analysis is based on observation of the immature stage development (days) in response to different water temperatures and type of containers. The general profile of the larval development based on water temperatures and container’s type were tabulated using mean number. The larval development to pupa was the fastest when the water temperatures increasing and also led by coconut shell in term of water container. In conclusion, the water temperature and type of containers were significantly (p-value < 0.05) affect the larval development days. This study concludes that the knowledge on the larval development’s factor is important in dengue control especially on the larval development days of Ae. aegypti.